Which rules to follow? how differences in renewable fuel standards obscure the potential climate impact of transportation fuels - Roux, Megan; Ekvall, Tomas; Schmidt, Jannick; Croxatto Vega, Giovanna (Frontiers in Energy Research, 2024)
Various regional and international standards have been developed to measure the environmental impacts of transportation fuels and minimize greenwashing and misinformation regarding their sustainability. These frameworks offer standardized methods and calculation guidelines for fuel producers to be able to verify compliance with predefined sustainability criteria and to achieve greenhouse gas emission reduction targets. However, significant inconsistencies exist among these standards in terms of methods, calculation rules, and default values assigned to specific fuels. This study reviews and analyses five fuel standards, namely the European Renewable Energy Directive, the United Nation's Carbon Offsetting and Reduction Scheme for International Aviation, the California Low Carbon Fuel Standard, the United States Renewable Fuel Standard, and the UK Renewable Transport Fuel Obligation. A qualitative analysis of the different schemes' methods identified several discrepancies. These were found to be primarily related to the modelling approach used, the burdens and credits arising from different feedstock types and co-products, and the modelling of electricity and land use changes. An example of this is that different standards provide credits for certain waste types, such as animal manure in the RED and RTFO, or municipal solid waste in CORSIA. In addition to the qualitative analysis, the carbon intensity was calculatedaccording to the rules set out by these frameworksfor case studies of eight fuel types, including biofuels and electrolysis-based fuels. These calculations further highlighted how the use of different fuel standards can lead to conflicting assessments of a fuel's environmental impact. Overall, our findings demonstrate substantial variations in the methods and calculation rules prescribed by the five standards, often resulting in markedly different carbon intensity scores for the same fuel. Based on this analysis, we propose specific changes to the calculation rules to enhance harmonization and improve the accuracy in reflecting the environmental consequences of fuel production and use. These recommendations include that indirect land use changes are always included, and more transparency regarding the methods for calculating the fuel carbon footprint.